2021
DOI: 10.1007/s11125-020-09526-6
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum response to the crisis

Abstract: Education is going through a period of crisis related to the SARS-CoV-2 pandemic that most probably will follow a continuum organized into distinct phases: emergency, recovery, reconstruction, development, and institutionalization. This article analyzes the response of curriculum to an unpredictable, chaotic, and recursive crisis situation. The article also highlights the role of important, but often forgotten, actors in a formal education system-parents-and examines the stresses the pandemic has placed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Self-assessed competence with the use of technology also correlated with how simple they considered the transition to ERTL to have been. Parents' level of education had been shown in other studies [38,45] to impact how well-prepared to support their children in learning activities they may feel, once again raising the matter of equity to awareness. This may also point to the need to invest not only in children's and teachers' digital competences [33,52] but also those of parents, who, as proxy educators [35], had to take on a fundamental role in ERTL.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Self-assessed competence with the use of technology also correlated with how simple they considered the transition to ERTL to have been. Parents' level of education had been shown in other studies [38,45] to impact how well-prepared to support their children in learning activities they may feel, once again raising the matter of equity to awareness. This may also point to the need to invest not only in children's and teachers' digital competences [33,52] but also those of parents, who, as proxy educators [35], had to take on a fundamental role in ERTL.…”
Section: Discussionmentioning
confidence: 92%
“…The empirical study presented here was based on a sample consisting mainly of women between 36 to 45 years old and with a post-secondary educational level. Since it is not a representative sample, the conclusions to be drawn from this research not only cannot be generalized but must also consider the specificity of this group of respondents [38,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study on curriculum responses to the crisis indicated that at the onset of the lockdown period, the global education system was in the emergency phase. With rapid closure of schools, education systems put in place temporary distance education measures targeted for emergency measures which are not necessarily part of a clear plan of action, aimed at minimizing the negative impacts on students' learning during the lockdown time (Charland et al, 2021)…”
Section: Aligning Teaching With Curriculummentioning
confidence: 99%
“…Everyone is familiar with the phrase of curriculum. A curriculum is a plan to accomplish objectives (Charland et al, 2021;Jonker et al, 2020;Matiisen et al, 2020). No matter how well-formulated the goals are, if the correct program is not in place to support them, they will not be realized.…”
Section: Introductionmentioning
confidence: 99%